Clinical and genetic characteristics and diagnosis of hereditary variants of neonatal epilepsy - N. A. Semenova; E. L. Dadali; A. A. Sharkov; I. A. Akimova (Нервно-мышечные болезни)
One of the most common neurological symptoms in children of the first year of life is seizures, the etiology of which is manifold. Investigations in recent years have shown that a significant number of infantile seizures are hereditary in nature. The review identifies the main groups of hereditary diseases and syndromes, in whose symptom complex convulsions are observed, outlines the main features of their clinical manifestations and methods of diagnosis. Correct and timely diagnosis of hereditary pathology helps not only to determine the nature of the course of the disease and the effectiveness of the use of various antiepileptic drugs, but also to significantly improve the effectiveness of genetic counseling of burdened families and to prevent the occurrence of recurrent cases оf disease.